From Service Quality To Patient Loyalty: A Scoping Review Of Healthcare Experience - Raras Purna Enrilladela; Ernawaty Ernawaty (Universitas Malahayati, 2026)
ABSTRACT The global shift toward patient-centered care has prompted healthcare providers to prioritize medical effectiveness and the quality of patient experience. This scoping review aims to map the relationship between service quality, patient satisfaction, and loyalty within healthcare facilities and identify the underpinning theories. Guided by the PRISMA-ScR protocol, this study analyzes 15 primary research articles published between 2021 and 2024. Findings reveal that service quality, reliability, empathy, physical infrastructure, and effective communication are key determinants of patient satisfaction. Furthermore, trust, percept value, and service equity enhance this relationship and trigger long-term loyalty, mainly through word of mouth. The three main theoretical frameworks, Expectancy Disconfirmation Paradigm (EDP), Equity Theory, and Value Percept Theory, are confirmed as critical to explaining patient satisfaction and loyalty. This review highlights the necessity of a comprehensive service management strategy that integrates technical, emotional, and relational dimensions to sustain patient loyalty. Keywords: Service Quality, Patient Satisfaction, Loyalty, Healthcare Facility.